Subdural and Cerebellar Hematomas Which Developed after Spinal Surgery: A Case Report and Review of the Literature. (11th July 2013) - Utku, Ufuk; Güler, Sibel; Yalnız, Erol; Ünlü, Ercüment
Abstract : Cerebellar hemorrhage following a spinal surgery is extremely rare; however, considering the localization, it can cause major clinical manifestations. While it is considered that these types of bleedings occur secondary to a venous infarct, the pathogenesis is still unclear. A 57-year-old male patient who underwent a laminectomy by exposing T12-L5 and had pedicle screws placed for ankylosing spondylitis developed a CSF leak due to a 2 mm dural tear. A hemorrhage with parallel streaks on the left cerebellar hemisphere was seen in CT scan, and a thin subdural hematoma at right frontotemporal region was seen on cranial MRI, performed after the patient developed intense headache, nausea, vomiting, and stiff neck in the early postoperative period. In this paper, a case of cerebellar and subdural hematomas following a spinal surgery is discussed with its clinical and radiologic findings.